Conflict Prevention and Reconstruction - World Bank (Washington, DC, 2012)
Those of us helping countries to build capacity to manage reconstruction after a conflict has ended need to be fully aware of the context in which we operate. Apart from the obvious destruction of infrastructure, presence of armed groups and difficult working conditions, there are several other characteristics of post-conflict conditions that we need to appreciate. First, civil conflicts seldom end in clear cut victories for one side. Post-conflict conditions are inherently unstable. There are winners and losers. The winners may have settled for less than they sought to achieve. Even if one side appears to have won, how the winner treats the defeated party will be critical to whether national reconciliation takes place and the sustainability of peace. A new government may be an unstable alliance of competing parties or consist of an uneasy collection of former fighters and technocrats who sat out the war in relative comfort abroad.